Identifying the relationship between self-esteem and satisfaction in a couple - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Miu, Anca Sabina (Technium Social Sciences Journal, 2021)
The need to see ourselves as good or adequate represents our need to experience increased self-esteem. As we develop as children, we become more and more aware of the power of our choices, but also of the responsibility generated by the choices we make. On our education, it is also one of the sources of self-esteem creation through the experience of being treated with respect by parents and other family members. As far as our own actions are concerned, one of the origins of creating personal self-esteem is the s28atisfaction we feel with our own choices considered moral, which are a particular aspect of satisfaction with our mental processes. The second pillar, the conception of oneself, is based on the opinion we have of ourselves, representing an assessment of our qualities and defects, founded or not. And the conception of oneself, as well as self-love, is formed in our family environment, the conception of oneself being mainly due to the projects that parents make for us.To be aware of the reasons for attraction to a person of the opposite sex can lead to the permanence of the valuing attitudes invested in the person of the opposite sex, which fuels new needs for knowledge and communication, or to the reduction of emotional tension by decreasing the need for the other. When physical and mental attraction increases with the knowledge of the other, with the proximity and physical and mental intimacy, this leads to the stabilization of the relationship and the desire to resume and intensify it. Mutual satisfaction becomes a condition for both maintenance and improvement of the attraction between the two partners, which is created by symmetry and reciprocity